2023
DOI: 10.21037/jtd-22-1706
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a diagnostic model based on left atrial diameter to predict postoperative atrial fibrillation after off-pump coronary artery bypass grafting

Abstract: Background This cohort study collected the clinical data of patients who underwent off-pump coronary artery bypass grafting (OPCABG) during hospitalization to observe the occurrence of postoperative atrial fibrillation (POAF), construct a POAF prediction model for CABG patients based on the left atrial diameter (LAD), and assist clinicians in making better medical decisions. Methods In this study, all patients who had no prior history of arrhythmia and who had received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Age, post-operative laboratory parameters including BNP and LDH were significantly higher in the AF group compared with the non-AF group (all P<0.05). It was reported that LAD independently associated with AF following CABG ( 11 ). Consistently, the present study revealed that LAD was markedly bigger in the AF group (38.83±4.91 vs. 37.13±4.28 mm, P=0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Age, post-operative laboratory parameters including BNP and LDH were significantly higher in the AF group compared with the non-AF group (all P<0.05). It was reported that LAD independently associated with AF following CABG ( 11 ). Consistently, the present study revealed that LAD was markedly bigger in the AF group (38.83±4.91 vs. 37.13±4.28 mm, P=0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al further explored the role of adding left atrial diameter to these existing predictive scores for AF post-cardiac surgery (CHA 2 DS 2 -VASc, POAF and HATCH). The authors found that the addition of left atrial diameter improved the predictive value of the POAF and HATCH scores but not the CHA 2 DS 2 -VASc score ( 8 ). With progressive left atrial dilatation, electrical remodelling of the left atrium leads to poor coordination of atrial contraction and the inability to maintain normal sinus rhythm.…”
mentioning
confidence: 99%
“…The incidence of POAF in isolated coronary artery bypass grafting (CABG) ranges from 13–33% ( 1 - 5 ). In patients undergoing isolated off-pump coronary artery bypass grafting (OPCABG), the incidence of POAF ranges from 8–20% ( 1 , 2 , 6 - 8 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations